The Prisoner’s Tattooed-Body as a Discursive Space (Andamios, Revista de Investigación Social, 2013)
The intention of this article is to show the results of a research that takes place in a penitentiary of Guanajuato State, Mexico. The theory and methodology that sustain this study is the critical social psychology, base of the Master Degree of Social Psychology on the Universidad Autónoma de Querétaro, Mexico. The conclusion is that the prisoner-subject involved in the routine, anonymity and lack of outlets to talk, chose tattoo his own body as a space of discourse, where can give significant and make sense of himself, of the situation he live, and also the leave permanent mark of his own story.
Keywords: Prison; Body; Tattoo; Discourse; Social Psychology